BENEVOLENT LEADERSHIP AND RESILIENCE IN DRIVING INNOVATIVE WORK BEHAVIOR: ROLE OF AN INNOVATIVE CLIMATE - Gunawan, Asep; Gartini, Siti; Priyono, Dadang (Jurnal Riset Bisnis dan Manajemen, 2026)
Innovation is essential for maintaining competitiveness in Indonesia's swiftly changing smartphone sector. Drawing on Social Exchange Theory (SET) and Conservation of Resources (COR) Theory, this study examines how benevolent leadership and employee resilience relate to innovative work behavior (IWB), with innovative climate conceptualized as a boundary condition. Using PLS-SEM on survey data from 221 employees of PT. Zhi Sheng Indonesia, the findings show that benevolent leadership and employee resilience do not exert significant direct effects on IWB. Instead, an innovative climate is positively associated with IWB and significantly moderates the relationship between benevolent leadership and innovative work behavior. These results indicate that benevolent leadership contributes to innovation primarily when embedded in an innovation-supportive climate that legitimizes experimentation and reduces perceived risk. The study extends SET and COR by demonstrating that relational and personal resources are necessary but insufficient for innovation without contextual activation.